FORMULASI EMULGEL EKSTRAK ETANOL DAUN JAMBU BIJI (Psidium guajava Linn.) SEBAGAI ANTI ACNE CLEANSER - Anindi Lupita Nasyanka; Janatun Na’imah; Norainny Yunitasari (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2020)
ABSTRACT Acne is a major problem for teenagers, especially at puberty. Guava leaves (Psidium guajava Linn .) are plants that contain several secondary metabolites, including the tannins, triterpenoids, glycosides, and flavonoids, which have anti-acne activity. So far, acne reduction is still being done using synthetic cosmetics. However, synthetic cosmetics often irritate, so that herbal cosmetics are an alternative. Formulation of herbal cosmetics for acne need to do. This study aims to determine the best formula for anti-acne cleanser emulgel from the ethanol extract of guava leaves based on the physical evaluation. Guava leaf extract as obtained by the maceration method uses ethanol as a solvent, then an emulgel was prepared with an extract concentration of F1 (5%) and F2 (10%). Emulgel characteristics were determined by physical evaluation including organoleptic, pH, emulsion type, viscosity, spreadability, homogeneity, foam stability, power clean, and hedonism. The best formula was determined by the number of tests that meet the requirements and are liked by consumers. The results had shown F1 is the best formula based on physical evaluation. Keywords: Acne, emulgel, guava leaves, physical evaluation